BOCHICA: Educational technologies for water care (2017)
This research project presents how the use of information technologies (IT) enhance learning variables for water care purposes in the province of Tequendama, Colombia. To achieve this goal, as part of Ingenieros Sin Fronteras (Colombia), we propose and develop two interactive technology solutions for the community, deploying them through the Casa Museo Tequendama (Tequendama, Colombia) foundation: a web video game and an augmented reality (AR) guided tour. Through this document, we present the context and problem to be solved, share the project's progress, what has been done and what is expected to be done in a near future.